Are We Treating The Patient or the Disease? - Eleanor Vogt; Patricia Shane; Henry Kahn (University of Minnesota Libraries Publishing, 2014)
The evidence abounds. A compelling body of research estimates that psychosocial stressors play a role in a significant number of patient complaints seen in primary care. In addition to the challenges faced by primary care clinicians who must consider their patients' psychosocial stressors, these factors can also affect pharmacists' care. Patient stress, through a number of mechanisms, can limit the efficacy of medicine as well as our efforts to achieve optimal medication management, and adds a poorly examined complexity to patient care practices. A landmark Institute of Medicine report calls for "whole patient "care, addressing psychosocial health needs, not as an embellishment, but as part of routine care. Whole patient care requires a fundamental shift, with patient needs at the center of healthcare delivery, and psychosocial-linked distress considered as integral to that model. These considerations place this topic squarely within the pharmacists' scope of practice and urgently call for an expanded approach to patient care and an opportunity for pharmacists to address that need. To parallel this discussion, the contributing role of practitioner stress is briefly reviewed.   Type: Idea Paper